Whole genome sequencing and characteristics of extended-spectrum beta-lactamase producing Escherichia coli isolated from poultry farms in Banaskantha, India - Patel, Mitul A.; Pandey, Aparna; Patel, A. C.; Patel, S. S.; Chauhan, H. C.; Shrimali, M. D.; Patel, Pankaj A.; Mohapatra, S. K.; Chandel, B. S. (Frontiers in Microbiology, 2022)
Worldwide dissemination of Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli constitutes an emerging global health issue, with animal food products contributing as potential reservoirs. ESBL E. coli infection is associated with the high mortality and mobility rate in developing countries due to less susceptibility to antibiotics. The present study aimed to elucidate the molecular characteristics and sequence-based analysis of ESBL E. coli in Gujarat state of India. This study included 108 E. coli strains isolated from different poultry farms (broiler and layer) in the Banaskantha District. The PCR method was employed to identify genotypic ESBL-producing antimicrobial resistance genes. Overall, a high prevalence of ESBL genes was found in poultry farms due to the high usage of antimicrobials. The PCR analysis revealed that 79.62% of isolates were detected positive with one or more ESBL genes. Among them, blaTEM (63.88%) was found to be the predominant genotype, followed by blaSHV (30.55%) and blaOXA (28.70%). In the blaCTX-M group, a higher prevalence was observed in blaCTX-M-9 (23.14%), followed by blaCTX-M-2 (24.07%) and blaCTX-M-1 (22.22%). We used whole-genome sequencing (WGS) method to evaluate the antimicrobial resistance genes, virulence factors, SNPs, plasmid replicons, and plasmid-mediated AMR genes of one ESBL E. coli isolate and examined the genetic relentlessness of a human pathogenic E. coli strain by comparing its sequence with broad geographical reference E. coli sequences. E. coli ST 681 was determined using multi-locus sequence typing. We compared our findings to the reference sequence of Escherichia coli str. K-12 substr. MG1655. We found 24,937 SNPs with 21,792 in the genic region, 3,145 in the intergenic region, and six InDels across the genome. The WGS analysis revealed 46 antimicrobial resistance genes and seven plasmid-mediated AMR genes viz., tetA, qnrS1, dfrA14, sul2, aph(3”)-lb, aph(6)-ld and Aph(3’)-la. The ST 681 was found to have Cib, traT, and terC virulence factors and two plasmid replicon, namely, IncFII(pHN7A8) and IncI1-I(Alpha). This study revealed a higher prevalence of ESBL E. coli detected from poultry.